Surface Ocean Warming Around Australia Driven by Interannual Variability and Long‐Term Trends in Southern Hemisphere Westerlies. Issue 9 (29th April 2020) - Duran, E. R.; England, M. H.; Spence, P.
Abstract: The ocean surface temperature and sea level response around Australia to both interannual variability as well as observed and projected changes in surface winds is presented. A hindcast ocean experiment shows interannual southward shifts in the Southern Hemisphere westerly winds drive ocean surface warming events in the South Australian Basin. Twenty‐first century climate and ocean projections in an ensemble of the fifth Coupled Model Intercomparison Project (CMIP5) models show that wind trends could play a role comparable in magnitude to that of radiative warming in driving surface ocean temperature change in this region. To evaluate the wind's role in these projected changes, we use an ocean experiment perturbed by the projected end of 21st century wind anomalies to show that the wind trends alone can generate approximately half of the ocean surface warming and sea level rise predicted by the CMIP5 models in the Tasman Sea. Plain Language Summary: This article demonstrates that both year‐to‐year variations and future projections in the Southern Hemisphere westerly winds are major drivers of surface ocean warming around Australia. Our research finds that year‐to‐year southward shifts in the westerly winds lead to surface ocean warming in the South Australian Basin. In future global warming projections human‐induced wind trends will also play a role, comparable in magnitude to the impacts of radiative warming in driving surface ocean temperature change around Australia. To evaluate the wind's role in these projected changes, we apply future wind projections to an ocean model experiment to show that the winds alone can create about half of the surface ocean warming and sea level rise predicted in future global warming projections. This research has important implications regarding the drivers of marine heatwaves and coastal sea level rise and suggests that monitoring changes in the wind circulation is critical to help understand and interpret future marine environmental changes. Key Points: Interannual southward shifts in Southern Hemisphere westerlies lead to surface ocean warming events in the South Australian Basin Twenty‐first century projected wind trends could play a role similar in magnitude to radiative warming in driving surface ocean temperature change Twenty‐first century wind trends are responsible for around half of the projected surface ocean warming and sea level rise in the Tasman Sea